2011
DOI: 10.1016/j.jtcvs.2011.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of pulmonary artery sarcoma

Abstract: Radical surgical resection provides the only chance of survival for patients with pulmonary artery sarcoma, and distal embolectomy may further extend survival for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…The prognosis of PAS is therefore extremely poor. The natural course of the disease is determined by local tumor growth as well as superimposed thrombosis and metastasized tumor embolus, leading to progressive obstruction of the pulmonary vessels [10], [11]. The median survival of time of untreated patients after diagnosis is 1.5 months (range 1.5–5.5 months) [12], [13].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of PAS is therefore extremely poor. The natural course of the disease is determined by local tumor growth as well as superimposed thrombosis and metastasized tumor embolus, leading to progressive obstruction of the pulmonary vessels [10], [11]. The median survival of time of untreated patients after diagnosis is 1.5 months (range 1.5–5.5 months) [12], [13].…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively reviewed their clinical records to evaluate the patient characteristics, perioperative findings, and postoperative outcomes. There were 14 articles, which reported at least 6 each, that identified 201 patients diagnosed with PAS, and 158 patients had detailed treatment and follow-up data [7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…They found that the 20 patients receiving PEA alone seemed to have a more prolonged survival duration than the 11 patients who underwent pneumonectomy [13]. Gan et al [14] concluded that only PAS resection without distal segmental pulmonary embolectomy might leave the superimposed thrombosis and metastasized PAS emboli, which lead to progressive obstruction in the distal segmental PA [29]. In their study, the median survival time of the five patients without distal embolectomy was 10 months; in contrast, the four patients who underwent distal embolectomy achieved 30-43 months of survival at follow-up.…”
Section: Pneumonectomymentioning
confidence: 99%
See 2 more Smart Citations